2021
DOI: 10.1088/2053-1591/ac3f5e
|View full text |Cite
|
Sign up to set email alerts
|

PLGA-based drug delivery system for combined therapy of cancer: research progress

Abstract: In recent years, PLGA micro/nano particle drug delivery systems has been widely used in cancer treatment. According to the unique properties of PLGA, carriers of various structures are designed to keep the function of drugs or bioactive substances, ensure the effective load of molecules and improve the bioavailability of drugs in diseased parts. PLGA is one of the earliest and most commonly used biodegradable materials. It is often used for functional modification with other polymers (such as polyethylene glyc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 175 publications
(203 reference statements)
0
16
0
Order By: Relevance
“…[3][4][5] In addition, a key reason for the failure of chemotherapeutic drugs in cancer treatment is mainly the multidrug resistance of cancer. [6][7][8] For a long time, researchers have been exploring and developing a variety of therapeutic methods, and drug vectors are an important aspect of them 9 , because they can effectively prevent drug degradation, deliver drugs to pathological sites, reduce toxic side effects, and improve therapeutic effects. There is a continuous need to meet current cancer treatment requirements by developing new drug delivery systems.…”
Section: Bing Yumentioning
confidence: 99%
“…[3][4][5] In addition, a key reason for the failure of chemotherapeutic drugs in cancer treatment is mainly the multidrug resistance of cancer. [6][7][8] For a long time, researchers have been exploring and developing a variety of therapeutic methods, and drug vectors are an important aspect of them 9 , because they can effectively prevent drug degradation, deliver drugs to pathological sites, reduce toxic side effects, and improve therapeutic effects. There is a continuous need to meet current cancer treatment requirements by developing new drug delivery systems.…”
Section: Bing Yumentioning
confidence: 99%
“…Several comprehensive reviews have discussed the use of PLGA as a drug delivery system for cancer therapy. [10][11][12][13] Here, this current review focuses on giving an overview of the recent progress in PLGA-based conjugated systems for the treatment of different cancers. The drug encapsulation studies of PLGA and FA-PEG-PLGA conjugates have also been discussed based on their chemistries, functionalized copolymers, preparation methods, and the structural coordination between the drug and the conjugate.…”
Section: Introductionmentioning
confidence: 99%
“…The experimental data demonstrated that electrospun nanofibers improve and accelerate the process of healing and thus offer a promising solution to the management of wounds. Additionally, electrospun nanofiber mats possess distinct, extraordinary characteristics, including excessive surface areas, a light weight, a porous network structure, and good stiffness and tensile strength, as compared to traditional fibers [ 44 , 45 ]. The electrospinning process can also produce nanofibrous mats with various structural assemblies, including nonwoven mesh, aligned mesh, patterned mesh, etc.…”
Section: Introductionmentioning
confidence: 99%
“…The electrospinning process can also produce nanofibrous mats with various structural assemblies, including nonwoven mesh, aligned mesh, patterned mesh, etc. [ 44 , 46 , 47 , 48 ]. In our previous study, we developed doxycycline-incorporated nanofibers and investigated their influence on the repair of ruptured tendons [ 49 ].…”
Section: Introductionmentioning
confidence: 99%